Metabolic hallmarks of liver regeneration. (September 2021) - Solhi, Roya; Lotfinia, Majid; Gramignoli, Roberto; Najimi, Mustapha; Vosough, Massoud
Abstract : Despite the crucial role of cell metabolism in biological processes, particularly cell division, metabolic aspects of liver regeneration are not well defined. Better understanding of the metabolic activity governing division of liver cells will provide powerful insights into mechanisms of physiological and pathological liver regeneration. Recent studies have provided evidence that metabolic response to liver failure might be a proximal signal to initiate cell proliferation in liver regeneration. In this review, we highlight how lipids, carbohydrates, and proteins dynamically change and orchestrate liver regeneration. In addition, we discuss translational studies in which metabolic intervention has been used to treat chronic liver diseases (CLDs). Highlights: During liver regeneration, metabolic biomolecules are dynamically regulated to provide the energy as well as anabolic molecules required for cell proliferation. Transient steatosis is a metabolic hallmark of the early phase of liver regeneration. Warburg effect enables intermediate biomolecules to initiate anabolic pathways for biomass generation. Hypoglycemia is a metabolic feature acting as a proregenerative signal for liver regeneration. The significance of metabolic events during liver regeneration has inspired researchers to investigate metabolic-targeted therapy for a variety of liver diseases in translational settings.